FEATURES OF EDUCATIONAL WORK IN THE PROCESS MILITARY TRAINING OF STUDENTS FOR THE PROGRAM OF RESERVE OFFICERS IN HIGHER EDUCATION EDUCATIONAL INSTITUTIONS - Kustinskyy, O.V. (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the peculiarities of bringing up of shulcnts which are taught in the reserve officers’ program. The author takes into consideration the modern demands of criteriavi lation and definition o f improving bringing up methods which provide its efficiency at the higher education establishment chair.